Further insights in trichothiodistrophy: A clinical, microscopic, and ultrastructural study of 20 cases and literature review - Ferrando, Juan; Mir Bonafé, José M.; Cepeda Valdés, Rodrigo; Domínguez, Anna; Ocampo Candiani, Jorge; García Veigas, Javier; Gómez Flores, Minerva; Salas Alanís, Julio César (2012)
Trichothiodistrophy (TTD) is a rare autosomal recessive condition that is characterized by a specific congenital hair shaft dysplasia caused by deficiency of sulfur associated with a wide spectrum of multisystem abnormalities. In this article, we study clinical, microscopic, and ultrastructural findings of 20 patients with TTD with the aim to add further insights regarding to this rare condition. Additionally, analyses of our results are compared with those extracted from the literature in order to enhance its comprehensibility. Materials and Methods: Twenty cases of TTD were included: 7 from Mexico and 14 from Spain. Clinical, microscopic, scanning electron microscopy (SEM) studies and X-ray microanalysis (XrMa) were carried out in all of them. Genetic studies were performed in all seven Mexican cases. Patients with xeroderma pigmentosum and xeroderma pigmentosum/TTD-complex were excluded. Results: Cuticular changes and longitudinal crests of the hair shaft were demonstrated. These crests were irregular, disorganized, following the hair longest axis. Hair shaft sulfur deficiency was disposed discontinuously and intermittently rather than uniformly. This severe decrease of sulfur contents was located close to the trichoschisis areas. Only five patients did not show related disturbances. Micro-dolichocephaly was observed in five cases and represented the most frequent facial dysmorphism found. It is also remarkable that all patients with urologic malformations also combined diverse neurologic disorders. Moreover, three Mexican sisters demonstrated the coexistence of scarce pubic vellus hair, developmental delay, onychodystrophy, and maxillar/mandibullar hypoplasia. Conclusions: TTD phenotype has greatly varied from very subtle forms to severe alterations such as neurologic abnormalities, blindness, lamellar ichthyosis and gonadal malformations. Herein, a multisystem study should be performed mandatorily in patients diagnosed with TTD.